2017
DOI: 10.1108/oir-10-2015-0331
|View full text |Cite
|
Sign up to set email alerts
|

Pleasure in the use of new technologies: the case of e-book readers

Abstract: Purpose -We analyse the adoption process of e-book readers and examine how the perception about the advantages of this technology and its incompatibility with consumer values determine the pleasure felt and its effective use. We also propose that consumer involvement with ICTs moderates these effects.Design/methodology/approach -Hierarchical moderated regression analysis is used to test the proposed model with survey data from a sample of e-book reader owners.Findings -Appraisal of the device's reading feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 53 publications
0
13
0
1
Order By: Relevance
“…There is only a significant difference between males and females for the factor perceived ease of use (Smeda et al, 2017). In addition to Smeda et al (2017), Anton et al (2017) also tested various determinants of how perception of technology and its suitability with consumer values figure out the pleasure in using e-books. The results of the regression analysis revealed that while free downloading and appraisal of the device’s reading features increase pleasure in using e-books, the frequency of the use of paper books decreases it (Anton et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is only a significant difference between males and females for the factor perceived ease of use (Smeda et al, 2017). In addition to Smeda et al (2017), Anton et al (2017) also tested various determinants of how perception of technology and its suitability with consumer values figure out the pleasure in using e-books. The results of the regression analysis revealed that while free downloading and appraisal of the device’s reading features increase pleasure in using e-books, the frequency of the use of paper books decreases it (Anton et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…When consumers feel relaxed and enjoy reading the advertorial, a positive attitude will be facilitated. As a result, this will lead consumers to accept the advertorial information and increase purchase intention (Antón et al , 2017). Chang et al (2014) suggested that emotional states constitute the critical factor in purchase behavior, but the attitude of acceptance also plays an important role in enhancing purchase intention.…”
Section: Discussionmentioning
confidence: 99%
“…The S–O–R framework suggests that when consumers encounter a stimulus (stimulus), a cognitive and emotional state (organism) will be aroused, which, in turn, determines behavioral responses involving approach or avoidance (response) (Antón et al , 2017). Mehrabian and Russell (1974) proposed the M–R model to explain how a store’s environmental stimuli lead to consumer approach or avoidance behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, Social Media (SM) have drastically changed the way both individuals and businesses operate [ 1 , 2 ]. In fact, SM usage goes beyond personal use and has entered both public and private sectors (e.g.…”
Section: Introductionmentioning
confidence: 99%